G196 Fluid supplementation in management of neonatal hyperbilirubinemia: a randomized controlled trial. (May 2019) - Mehta, A; Goyal, P; Chawla, D; Malik, B
Abstract : Background: Neonatal hyperbilirubinemia needing treatment is the most common morbidity in neonates. Underlying cause of jaundice cannot be found in up to half cases. Suboptimal feeding resulting in dehydration is an important aggravating factor in neonatal hyperbilirubinemia. Objective: To evaluate the efficacy of intravenous or oral fluid supplementation in increasing the percent fall of serum total bilirubin in healthy term and late preterm neonates with hyperbilirubinemia being managed by intensive phototherapy. Methods: Design: Openlabel randomized controlled trial. Setting : Tertiary care neonatal unit of a teaching hospital. Participants and intervention : Late preterm and term neonates with severe hyperbilirubinemia were randomized to receive 50 ml/kg of intravenous fluid over 8 hour (IVF group, n=51), 50 ml of oral rehydration solution over 8 hours (ORS group, n=50) or only standard therapy (Control group, n=49). Standard treatment with intensive phototherapy according to American Academy of Pediatrics guidelines was administered in all the three study groups. Main outcome measure : Percent decline in serum total bilirubin (STB) over 8 hour of intervention. Results: Baseline variables were comparable in the three study groups. Over 8 hours of intervention, STB declined by 15.5% (95% CI: 11.7% to 19.4%) in the IVF group, by 9.1% (95% CI: 7.3% to 10.9%) in the ORS group and by 8.0% (95% CI: 6.2% to 9.7%) in the control group. Percent decline in STB was greater in IVF group as compared to ORS and control groups. However, duration of phototherapy and number of neonates needing exchange transfusion were comparable in the three study groups. Conclusions: Intravenous fluid supplementation may result in faster decline of STB in first few hours of treatment. However, with use of intensive phototherapy, there was no effect on overall duration of phototherapy or need of exchange transfusion.